Efficiency of Trichoderma viride as a biocontrol agent for Phytophthora capsici in Pepper (Capsicum annuum L.) - Romero, V. (2022)
Phytophthora capsici is one of the most devastating pathogens that limits the production of Paprika (Capsicum annuum L.) worldwide. Likewise, Trichoderma viride stands out as a biological agent due to its antagonistic effect, resistance inducer, growth stimulator, etc. The present work evaluated the effectiveness of T. viride as a biocontrol agent against P. capsici in Paprika using three growth methods (direct seeding, plantlet and bare root). Twelve treatments were developed under greenhouse conditions, including a control (without inoculum) and a completely randomized design with a factorial arrangement. T. viride inoculation was carried out 40 days after sowing at a concentration of 106 conidia ml-1 while P. capsici was inoculated 50 days after sowing using three colonized wheat grains per plant. The inoculation method of the controlling agent in the direct seeding and plantlet was given by drench, and in the bare root was carried out by immersing of the seedling for 5 minutes prior to the transplant. Then, the correlation between plant growth method and P. capsici, and the interaction between T. viride and the plant growth method were made. The results showed that the highest efficacy of T. viride as a P. capsici biocontrol agent was in the method of the plantlet and bare root. The correlation between the method of growing crop and root rot was lower in bare root (74 % severity). In the other two treatments (direct seedling and plantlet) 100 % of plants were dead; finally, the effect of T. viride as a growth inducer was not evidenced in any of the treatments. Regarding AUDPC, the direct seeding method showed a higher incidence. The bare root planting method obtained the lowest value of the T. viride and P. capsici interaction.